PESANTREN IN DYNAMIC TRANSFORMATION: Harmonizing Classical Roots and Modern Practices - Sofi, Muhammad Jauhari; Manaf, Sofwan; Ali, Jauhar (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
Caught between the pull of tradition and the push of modernity, pesantren is undergoing a crucial transformation in the landscape of Indonesian Islamic education. This study explores how pesantrens maintain their classical roots while integrating modern educational practices. It employs a narrative review with data collected from relevant peer-reviewed literature. These data are synthesized according to common themes and analyzed qualitatively. The review reveals that, despite external pressures (e.g., colonial rule and state policies) and its active role in civil society, pesantren continues to preserve traditional Islam by sustaining classical Islamic scholarship, moral teachings, and kyai-led authority. At the same time, modernization has strongly influenced pesantren education, with many institutions expanding their curricula, adopting inclusive governance, utilizing digital tools, and aligning with national education policies to strengthen institutional capacity and relevance. These pesantrens demonstrate a careful balancing act; they selectively integrate modern educational reforms while upholding their religious traditions although certain issues still merit further attention. Overall, these findings underscore the pesantren’s resilience, adaptability, and significance in today’s Indonesian educational context.